问题
解答题
计算: (1)(-4a)•(ab2+3a2b-1); (2)(
(3)(a2+3)(a-2)-a(a2-2a-2) (4)(2x-y)2-4(x-y)(x+2y). (5)(a+b-1)2; (6)[(3x+2y)(3x-2y)-(x+2y)(5x-2y)]÷4x. |
答案
(1)原式=-4a•ab2+(-4a)•3a2b+(-4a)•(-1)
=-4a2b2-12a3b+4a.
(2)原式=
x6y2÷(-0.6xy)+3 4
x3y5÷(-0.6xy)+(-0.9x2y3)÷(-0.6xy)6 5
=-
x5y-2x2y4+5 4
xy2.3 2
(3)原式=a3-2a2+3a-6-a3+2a2+2a
=5a-6.
(4)原式=4x2-4xy+y2-4x2-8xy+4xy+8y2
=-8xy+9y2.
(5)原式=[(a+b)-1]2
=(a+b)2-2(a+b)+1
=a2+b2+2ab-2a-2b+1.
(6)[(3x+2y)(3x-2y)-(x+2y)(5x-2y)]÷4x
=[9x2-4y2-5x2+2xy-10xy+4y2]÷4x
=(4x2-8xy)÷4x
=x-2y.